Lysozyme-like enzyme from the scallop Chlamys islandica - MT Viana; J Raa (Ciencias Marinas, 1992)
A lysozyme-like enzyme isolated from the crystalline style of the scallop Chlamys islandica, was purified by cation exchange chromatography on carboxymethyl cellulose and Mono S columns. The enzyme was optimally active at pH 4.8, similar to that observed for the lysozyme of Mytilis edulis. The present enzyme has an unusual 67%, remainder activity at 4ºC when cell walls of Micrococcus lysodeikticus were used as substrate. The enzyme had a specific activity of 486,090 U/mg, corresponding to ten times higher than 1ha1 of hen egg while lysozyme.